2017
DOI: 10.1007/s00264-017-3431-4
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in the diagnosis and management of extra-articular hip impingement syndromes

Abstract: Purpose Extra-articular hip impingement syndromes encompass a group of conditions that have previously been an unrecognised source of pain in the hip and on occasion been associated with intra-articular hip impingement as well. As arthroscopic techniques for the hip continue to evolve, the importance of these conditions has been recognised recently and now form an important part of the differential of an individual presenting with hip pain. The aim of this article, therefore, is to provide the reader with an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 69 publications
0
49
0
3
Order By: Relevance
“…Vandenbussche et al reported that the depth of the psoas valley is approximately 4 mm from the acetabular equator [1,2], which is almost the same as the degree of superomedialization in the acetabula when reaming during a THR [20]. Therefore, pre-and intra-operative assessment of the psoas valley is essential to avoid postoperative iliopsoas impingement which is becoming a major issue following arthroplasty [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Vandenbussche et al reported that the depth of the psoas valley is approximately 4 mm from the acetabular equator [1,2], which is almost the same as the degree of superomedialization in the acetabula when reaming during a THR [20]. Therefore, pre-and intra-operative assessment of the psoas valley is essential to avoid postoperative iliopsoas impingement which is becoming a major issue following arthroplasty [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…It is often difficult to determine the specific causes of groin pain [9]. Extra-articular subspine impingement at the level of the anterior inferior iliac spine (AIIS) has been reported as a cause of groin pain in the nonarthritic hip [10]. We describe a similar entity as a potential cause of refractive periarticular pain in the groin to the lateral hip region after THA: extra-articular impingement (EAI) between the AIIS and the anterior part of the GT.…”
Section: Introductionmentioning
confidence: 90%
“…As for other factors, Vandenbussche et al reported that the depth of the psoas valley is approximately 4 mm from the acetabular equator [1,2], which is almost the same as the degree of superomedialisation in the acetabulae when reaming during a THR [19]. Therefore, pre-and intra-operative assessment of the psoas valley is essential to avoid postoperative iliopsoas impingement which is becoming a major issue following arthroplasty [20][21][22].…”
Section: F) Related Factorsmentioning
confidence: 99%